Significance of a positive Clostridium difficile toxin test after hematopoietic stem cell transplantation. Issue 6 (21st April 2016) - Akahoshi, Yu; Kimura, Shun‐ichi; Nakano, Hirofumi; Harada, Naonori; Kameda, Kazuaki; Ugai, Tomotaka; Wada, Hidenori; Yamasaki, Ryoko; Ishihara, Yuko; Kawamura, Koji; Sakamoto, Kana; Ashizawa, Masahiro; et al.
Abstract: Patients with hematological malignancies show a high prevalence of asymptomatic colonization with Clostridium difficile (CD colonization). Therefore, it is difficult to distinguish CD colonization with diarrhea induced by a conditioning regimen from true Clostridium difficile infection (CDI) in hematopoietic stem cell transplantation (HSCT) recipients. We retrospectively analyzed 308 consecutive patients who underwent a CD toxin A/B enzyme immunoassay test for diarrhea within 100 d after HSCT from November 2007 to May 2014. Thirty patients (9.7%) had positive CD toxin results, and 11 of these had positive results in subsequent tests after an initial negative result. Allogeneic HSCT, total body irradiation, stem cell source, acute leukemia, and the duration of neutropenia were significantly correlated with positive CD toxin results. In a logistic regression model, allogeneic HSCT was identified as a significant risk factor (odds ratio 18.6, p < 0.01). In an analysis limited to within 30 d after the conditioning regimen, the duration of neutropenia was the sole risk factor (odds ratio 10.4, p < 0.01). There were no distinctive clinical features for CDI, including the onset or duration of diarrhea. In conclusion, although CDI may be overdiagnosed in HSCT recipients, it is difficult to clinically distinguish between CDI and CD colonization.